Instagram as a Platform for Change in Environmental Campaigns - Sari, Meliana (Cultural Narratives, 2024)
This research aims to explain and describe the eco-lexicon that exists in one of the “Reach for a Greener Tomorrow” campaign posts in @sayapilihbumi Instagram posts that contain eco-lexicon and have issues related to the environment. The theory used in this research is Greening the media (Maxwell et al., 2013) which states that Greening media is a study that begins by acknowledging a historic responsibility to face the challenge of the ecological crisis as a fundamental challenge to critical scholarship in the field and uses an ecolinguistics perspective approach, in the form of analyzing ideological, sociological and biological meaning in eco-lexicons in @sayapilihbumi posts. The   method   used   in   data   collection   is   documentation   and   observation   on   the @sayapilihbumi Instagram account. The result of this research indicates that the eco-lexicons serve not only as a means of communication but also as tools for fostering environmental awareness and encouraging sustainable practices among followers. The findings suggest that social media campaigns can effectively influence public perceptions and behaviors regarding environmental issues, thereby contributing to a broader movement towards sustainability. This study underscores the importance of language in shaping ecological consciousness and advocates for the continued use of social media as a platform for environmental advocacy. By understanding the meanings behind eco-lexicons, stakeholders can better design campaigns that resonate with audiences and promote actionable change.